Pengembangan Sistem Informasi Akademik Pada Pondok Pesantren Minhajurrosyidin Gresik - Ferina Kusuma Anjani; Bayu Rahayudi; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Abstract Information technology which is increasingly sophisticated certainly brings a lot of convenience to humans. So that technology is widely applied in various fields. One of them is in the field of education. Both formal and non-formal education requires a computerized system to support academic activities to be more effective and efficient. The purpose of making this system is to overcome the problems that exist in the previous system which was considered inefficient so that a website-based academic information system was created at the Minhajurrosyidin Gresik Islamic boarding school. With the existence of this academic information system it is able to provide facilities for teachers / administrators in processing and storing data in Islamic boarding schools so that they become more effective and efficient. This academic information system covers student data, teacher / teacher data, and student assessment and SMS Gateway. Making information systems using the help of the Laravel framework, using the PHP JavaScript programming language, and CSS in making system interfaces and for storing data used MariaDB software.